The analisis of the standards for decision of surgical treatment proximal humeral. Anatomical research - B. E. Gurkin; D. V. Ivanov; A. S. Kalintsev; M. G. Fabricant (Кубанский научный медицинский вестник, 2014)
The article provides information about habits of the routes to the proximal humeral for people with different constitution. The clinical studies were made on 55 corpses, which were put in order of constitution, body mass and shoulder-elbow length. Results of studies have shown us that for people with normal body mass better to use anterior approach in a case of fracture with breaking of the proximal humerus, transdeltoid rout for people with transvers fractures of collum and low bone mineral density. As for people with subnormal body an anterior approach is more convenient than transdeltoid rout, and for patients with overweight and lipotrophy of the I degree selection of the rout depends on character of the fracture and optimal method of the osteosynthesis.